O Instagram do Theatro Municipal do Rio de Janeiro e a comunicação com seu público - Fernandes, Leandro de Melo (2025)
This dissertation sought to observe the communication of the Theatro Municipal do Rio de Janeiro through its Instagram. The social network is currently used as the institution's main communication channel, together with its official website. The research analyzed its communication and other activities developed by the institution. Statistical data analysis tools related to the number of followers, likes and engagement were used; semi-structured interviews with its president and communications advisor; and a questionnaire was applied to the audience at three different shows. In addition, it observed how the cultural institution of the last century communicates today.